Preparation of a Nitrite Electrochemical Sensor Based on Polyaniline/ Graphene‑Ferrocenecarboxylic Acid Composite Film Modified Glass Carbon Electrode and its Analytical Application - Wei,Yuli (2015)
A sensitive and stable electrochemical sensor based on polyaniline/graphene-ferrocenecarboxylic acid (PANI/GR-FCA) composite film modified glass carbon electrode for determination of nitrite was presented and its morphology and structure were characterized by scanning electron microscope (SEM), transmission electron microscope (TEM), Fourier transform infrared spectroscopy (FTIR) and X-ray powder diffraction (XRD). Cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques were used to investigate the electrochemical behavior of the nitrite oxidation, which exhibited an enhanced voltammetric response at the modified electrode. In the optimal condition, the oxidation of nitrite in Britton-Robinson buffer solution (BR) of pH 4.0 had the higher peak current than the bare electrode. A linear calibration curve over the concentration range 0.4-300 µmol L-1 of nitrite were obtained with a linear regression equation I (µA) = 0.1589 + 0.0020C (µmol L-1) (R = 0.9991, n = 13) and the detection limit was down to 0.02 mmol L-1 (S/N = 3). The recoveries of all determinations ranged between 96-102%. At the same time, the modified electrode showed a good long-term stability and reproducibility for determination of nitrite, as well as high selectivity.